重写中国近代史：二十世纪九十年代早期对现代性的回应 = Rewriting modern chinese history : echoing the modern during the early 1990s - van Dongen, Els (Zhonghua Book Company, 2016)
The end of the Cold War and the implosion of the Soviet Union, the Tiananmen Incident of June 1989, and the initiation of the second reform period with Deng Xiaoping’s Southern Tour (nanxun) in early 1992 urged Chinese intellectuals to rewrite modern Chinese history. Even though scholars such as Li Zehou and Liu Zaifu famously said “goodbye to revolution” (gaobie geming) in 1995, the rewriting of history also took the form of rejections of “radicalism” (jijin zhuyi) as a reform strategy. Several scholars identified “radicalism” as the core trait of what is perhaps twentieth-China’s most famous intellectual, cultural, and political movement: the May Fourth Movement. Disclaiming the May Fourth heritage, rejections of “radicalism” characterized the thought of neo-conservatives, New Confucians, and cultural nationalists alike. The chapter discusses some of the manifestations of “anti-radicalism” of the early 1990s and argues that even though they are not representative of a conservative trend because the notion of progress remained unquestioned in the context of transition and crisis, they do reveal an important turn towards the concern with historical continuity that is still visible today.